Implementasi Karakter Peduli Sosial sebagai Pengamalan Nilai-Nilai Pancasila dalam Komunitas Motor Vespa (Studi di Komunitas Vespa Antique Club Indonesia Cabang Bandung) - Beben Muhammad Bachtiar (Universitas Kuningan, 2023)
In this era of globalization, the values of social care continue to experience degradation, especially among the younger generation or among students who are the nation's successors. The values of social care that are currently starting to fade are examples of indifference, self-defeating attitudes, disloyalty to friends and so on. This study aims to find out that there are still those who implement the character of social care which is used as the practice of Pancasila values carried out by the Vespa motorbike community. The method used in this research is a descriptive study with a qualitative approach. The research was conducted at the Bandung branch of the Vespa Antique Club Indonesia community. Research informants consisted of founders, administrators, and members of the Bandung branch of the Vespa Antique Club Indonesia as well as the community and orphanage caretakers. The results of data collection obtained through interviews, observation, literature and documentation techniques were then analyzed using analytical techniques in the form of data reduction, data presentation, and verification then validated using source triangulation techniques and data collection techniques. The results of the study show that the vespa motor community implements the social care character as the values of Pancasila. It has a goal in its community to serve the nation and the state. In addition, the character that is instilled in the souls of each of its members is an education that creates a high sense of solidarity for each of its members, which aims to to cultivate a high sense of concern for fellow human beings. With various forms of activities and work programs that are used as a form of implementing a socially caring character in the process many positive things can be taken for all members in particular and for society in general.